Sistem Monitoring Proses Pengasinan Telur Asin Berbasis IoT (Studi Ka-sus Industri Telor Asin Batammas Kota Brebes) - Zafia, Anggi; Novantoro, Setiawan Dwi; Nur Utomo, Aulia Desy (STKIP PGRI Tulungagung, 2024)
Batammas Salted Egg Shop is a salted egg manufacturing industry lo-cated in Bumiayu, Brebes Regency experiencing problems in the salted egg salting process due to calculations and salting procedures related to conditions that affect the quality of salted eggs such as measuring the saltiness of dough to coat duck eggs, determining the temperature of the storage place, salting time, and determining the quality of salted eggs, It is still done by estimation based on human or manual senses which causes a lot of dough ingredients to remain after use, the failed salting egg salting process, and the lack of time efficiency in determining the quality of salted eggs. From these problems, a system was made to find out the conditions during the IoT-based salted egg salting process using NodeMCU ESP8266 as a microcontroller and 3 supporting sensors, namely DHT11 sensors, TDS sensors and BH1750 sensors, using the waterfall method as the flow of making the system with the results of a system with an average temperature value of 27.82o C with good sta-tus, salt content that requires 4 times the addition of a total salt of 4500 grams of salt for 64 grains (4.48 kg) salted eggs with good final status, as well as a good determination of the quality of salted eggs, which is 4500-4700 lux with the result of 60 salted eggs of good quality and 4 salted eggs of poor quality or damaged.